The Effect of Freeze Dried Lactobacillus acidophilus Culture Concentration an Microbiological and Organoleptic Characteristics of Synbiotic Biscuits Made From Sorghum Flour and Soybean Flour - Een Sukarminah; Endah Wulandari; Debby Moody Sumanti; Efri Mardawati; Elazmanawati Lembong; Okta Paulia (Journal of Industrial and Information Technology in Agriculture, 2017)
Sorghum flour and soybean flour can be processed as the main raw material in the manufacture of functional food product, namely synbiotic biscuits with addition of freeze dried Lactobacillus acidophilus culture. The purpose of study was to determine the concentration of freeze dried L. acidophilus culture on synbiotic biscuits made from sorghum flour and soybean flour with the best microbiological and organoleptic characteristics. The research method used was randomized block design with 4 treatments and 3 replications. The treatments were the freeze dried L. acidophilus concentration 8%, 10%, 12%, and 14%. The results of study showed that the addition of freeze dried culture of L. acidophilus to the synbiotic biscuits made from sorghum flour and soybean flour gave a significant different effect on total L. acidophilus probiotic bacteria, aroma and yield, but did not give a significant effect on the color, taste and texture preferences. Synbiotic biscuits made from sorghum flour and soybean flour with the addition of freeze dried L. acidophilus concentration of 14% (w/w) were selected as the synbiotic biscuit with the best characteristic with total bacterial content of probiotics 10,67 Log CFU g-1, were perceived a bit like to like by the panelist and the obtained yield was 92,14%.